2014
DOI: 10.1186/preaccept-5912484341258228
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of macrocyclic lactone resistant Dirofilaria immitis isolates in experimentally infected laboratory dogs

Abstract: Background: Strains of Dirofilaria immitis suspected of lack of efficacy (LOE) to macrocyclic lactone (ML) preventive drugs have been increasingly reported in dogs by practicing veterinarians since 2005 in the Lower Mississippi Delta region. If proven, and not controlled in the early stages, the emergence of ML drug resistance threatens to become a widespread problem in the US that may limit the effectiveness of current preventive drug treatment methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 24 publications
0
53
0
Order By: Relevance
“…Given the importance of the macrocyclic lactones in the control of heartworm and human filariases, together with the emergence of resistance to the drugs in D. immitis (Bourguinat et al 2015; Wolstenholme et al 2015; Pulaski 2014; Geary et al 2011) and reports of reduced drug efficacy in some Onchocerca volvulus patients (Osei-Atweneboana et al 2011) it is essential that we understand how they work against these parasites. Bioinformatic analysis indicates that filarial species have lost many genes encoding ligand-gated ion channels, including many of the GluCl-encoding genes, when compared to other nematodes (Williamson et al 2007; Beech and Neveu 2015).…”
Section: Anthelmintic Effects Of Macrocyclic Lactones In Filarial Infmentioning
confidence: 99%
“…Given the importance of the macrocyclic lactones in the control of heartworm and human filariases, together with the emergence of resistance to the drugs in D. immitis (Bourguinat et al 2015; Wolstenholme et al 2015; Pulaski 2014; Geary et al 2011) and reports of reduced drug efficacy in some Onchocerca volvulus patients (Osei-Atweneboana et al 2011) it is essential that we understand how they work against these parasites. Bioinformatic analysis indicates that filarial species have lost many genes encoding ligand-gated ion channels, including many of the GluCl-encoding genes, when compared to other nematodes (Williamson et al 2007; Beech and Neveu 2015).…”
Section: Anthelmintic Effects Of Macrocyclic Lactones In Filarial Infmentioning
confidence: 99%
“…However, there have been reports of loss of efficacy (LOE) of these MLs against heartworm in the USA, especially in those areas where heartworm challenge is high (Hampshire, 2005). Recent studies have confirmed, using in vivo efficacy studies and genetic analysis, actual ML resistance in D. immitis (Bourguinat et al., 2011a, Bourguinat et al., 2015, Pulaski et al., 2014). There also exists some evidence of ML resistance in the human parasite, Onchocerca volvulus (Osei-Atweneboana et al., 2007, Osei-Atweneboana et al., 2011, Nana-Djeunga et al., 2012, Nana-Djeunga et al., 2014, Pion et al., 2013), a filarial nematode which is closely related to D. immitis .…”
Section: Introductionmentioning
confidence: 99%
“…In dogs experimentally infected with two different heartworm isolates taken from suspected lack-of-efficacy cases from the Delta region, the parasites survived repeated treatment with a macrocyclic lactone. The dogs received double the recommended dose, monthly for six months, under the watchful eye of veterinarians 4 . "There's no question that these are resistant parasites, " says Wolstenholme, who has had similar findings in his own research into resistant strains.…”
Section: Rumour Versus Realitymentioning
confidence: 99%